Perancangan Interior Kafe Dan Resto The Historic Of Blitar - Puspoyo, Aditya Chandra (Intra, 2015)
Nowadays, places like restaurants or cafÃ© are very popular for middle-upper class and middle-lower class society for meetups, business, or to just simply sit back and relax, even in areas and cities in Indonesia that are still developing, for example; Blitar city. However, in those developing cities, those places are mostly still under-developed, and besides, most of the visitors who came to Blitar are only familiar with the tourists destinations without knowing the origins or the history of Blitar city. Blitarâs interesting heritage of local legends will be relived and applied to the restaurantâs design concept, so this place can also be used as information centre of Blitar, considering the lack of that kind of places in the city. This interior design is also as a renovation for the place with the goal of improving the interior elements and systems that still havenât expressed the concept of Blitar, therefore, this design will use the concept of âTime Travelâ to answer the currently existing problems.